The eyes as the exclamation mark of the face: exploring the relationship between eye size, intensity of female facial expressions and attractiveness in a range of emotions - Esté Jaloveckas, Alanís; Granero, Roser (Frontiers in Psychology, 2024)
Background-objective: The eyes play an important role in communicating emotions and shape the determination of other facial attributes. Here, we explored the relationship between eye size, perceived intensity and attractiveness of facial expressions.Methods: A sample of N=63 participants (men and women, aged 18 to 35) rated attractiveness and emotional intensity for images displaying emotionally expressive women's faces with digitally manipulated eye size (15% smaller, unchanged, or 15% larger).Results: The analysis of perceived intensity showed an interaction parameter between eye size and gender. Female individuals reported differences when comparing unchanged and larger eyes; male participants showed differences across all eye size comparisons (smaller-unchanged, smaller-larger, unchanged-larger). Regarding perceived attractiveness, faces with smaller eyes registered lower mean scores than both unchanged and larger. The lowest intensity level was associated with neutral faces and the highest with fearful ones. Faces displaying happiness were perceived as the most attractive.Conclusion: Larger eyes seem to make emotions more intense and attractive. We suggest that the more intense phenomenon serves an evolutive purpose, as it might encourage caretaking behavior.